(untitled) (Washington, D.C., 2013)
The World Bank supports countries around the world in mainstreaming a comprehensive and integrated approach to disaster risk management into development. The World Bank provides analytical and advisory services, helps to build climate and disaster resilience into core investments across sectors, and offers unique financial solutions to better manage the contingent fiscal risks from disasters.
Keywords: Emergency management,Emergency management,Disasters,Disasters,Quản lý khẩn cấp,Quản lý khẩn cấp,Thiên tai,Thiên tai; Economic aspects,Social aspects,Khía cạnh kinh tế,Khía cạnh xã hội; Pacific Area,East Asia,Khu vực Thái Bình Dương,Đông Á